Robust neutralization of emerging JN.1 subvariants by the updated JN.1 vaccine: rationale for catch-up booster recommendations in high-risk individuals - Choi, Ju-yeon; Kim, Su-Hwan; Park, Soyoung; Jang, Hye Min; Lee, Young Jae; Kim, Hye-Jin; Kim, Dokeun; Ko, Jae-Hoon; Jeong, Hye-Sook (Frontiers in Immunology, 2026)
The updated JN.1 monovalent vaccine (MoV) for the 2024–2025 season elicits strong cross-neutralizing activity against subsequently circulating SARS-CoV-2 variants in 2025, including the recently emerging NB.1.8.1, with titer increases comparable to those against the vaccine strain JN.1. The immune response induced by the JN.1 MoV was markedly stronger than that induced by XBB.1.5 MoV in the previous season, both against the vaccine strain and post-vaccine variant (all P < 0.001). These results likely reflect improved background immunity to circulating variants and support the use of catch-up booster vaccination during the summer surge, particularly for high-risk groups.